MAPPING THE FISHERIES RESOURCES MANAGEMENT: A NATURAL RESOURCES ACCOUNTING APPROACH - Sutrisno, Dewayany; Nahib, Irmadi; Dewi, Ratna Sari (GEOMATIKA, 2010)
Marine resources, especially capture fisheries, become one of the leading sector that need to be improved for the future of national economy. For the need of capture fisheries management, a mapping model should be employed to provide such user friendly information of fisheries sector to the local or national government. Fisheries resources accounting map can fulfill this need by giving some reliable information. Using Poso in Central Celebes province, a model was developed to meet the need of information. The result indicates the prospect of capture fisheries can be developed for further local fishermen prosperity and local regional income. Indeed, the result also indicates the fisheries resource accounting map, a spatial information model, is good tool in providing condition and possible management of capture fisheries sector.Keywords: capture fisheries, fisheries accounting, spatial modelABSTRAKSumberdaya laut, terutama sektor perikanan tangkap merupakan sektor utama yang harus terus ditingkatkan guna menunjang peningkatan pendapatan ekonomi negara. Untuk keperluan manajemen perikanan tangkap ini, maka dirasakan sangat perlu dibuat suatu model spasial guna mendukung program perikanan yang berkesinambungan. Akutansi sumberdaya perikanan dapat memenuhi kebutuhan ini melalui pemodelan ekologi-ekonomi. Sebagai studi kasus digunakan perairan pesisir daerah Poso, Sulawesi Tengah. Hasil yang diperoleh menunjukan, bahwa melalui pemodelan spasial ini dapat dilihat prospek sektor perikanan tangkap untuk meningkatkan kesejahteraan nelayan dan pendapatan pemerintah kabupaten. Selain itu, hasil kajian ini juga memperlihatkan peran model spasial akutansi sumberdaya perikanan sebagai alat yang dapat diandalkan untuk menunjang manajemen perikanan tangkap. Kata Kunci: perikanan tangkap, akuntansi perikanan, model spasial